Grazing behaviour, intake, digestion, performance and endoparasitic infection of lambs raised at different stocking rates under low-input farming systems - Kantzoura, Vaia; Hadjigeorgiou, Ioannis; Goulas, Christos; Zabeli, Georgia; Sotiraki, Smaragda; Zervas, Georgios (Journal of the Hellenic Veterinary Medical Society, 2022)
Twenty-four Boutsiko breed lambs were allocated to three groups of equal average live weight (LW: 20.8 kg) and pastured at three stocking rates: SR1, SR2 and SR3 (representing 60, 80 and 100 lambs/ha respectively) under low-input farming practices. Animals were grazed on a semi natural sward daily, during a 60 days period. Sward height in all treatments remained above 7 cm during the trial and the herbage gross chemical composition was similar between treatments. On average, the lambs grazed 372 min, ruminated 140 min and spent 88 min on other non-feeding activities during the daily pasturing. Lambs consumed at the start and the finish of the trial 714 g and 1014 g of herbage DM/day, or 70.5 and 99.0 g/kgW0.75/day respectively. Herbage DM digestibility (in vivo) was moderate averaging 61% and no differences were observed between the three groups of lambs. The daily live weight gain of lambs (DLWG) was different (p<0.01) between the stocking rates, where lambs on plot SR1 had the highest gain (0.0918 kg LW/day) and lambs on SR2 and SR3 plots the lowest gain (0.0344 and 0.0531 kg LW/day respectively). Faecal egg counts (FEC) for gastrointestinal parasites (GIN) from lambs grazing plot SR3 were low, while high numbers of Moniezia spp. eggs were present in faecal samples of all groups of lambs at the end of the experiment. It is concluded that lamb fattening on pasture can be achieved at reasonable stocking rates, without the use of anthelmintics, if a local hardy breed is used.